2021
DOI: 10.2196/30971
|View full text |Cite
|
Sign up to set email alerts
|

Infodemic Signal Detection During the COVID-19 Pandemic: Development of a Methodology for Identifying Potential Information Voids in Online Conversations

Abstract: Background The COVID-19 pandemic has been accompanied by an infodemic: excess information, including false or misleading information, in digital and physical environments during an acute public health event. This infodemic is leading to confusion and risk-taking behaviors that can be harmful to health, as well as to mistrust in health authorities and public health responses. The World Health Organization (WHO) is working to develop tools to provide an evidence-based response to the infodemic, enabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 22 publications
0
45
1
Order By: Relevance
“…Methodological approaches can range from our simple Q&A format to the World Health Organization's highly sophisticated machine learning-driven social listening of large social media platforms. 5 Our methods provide proof-of-concept that even simple efforts to elicit community feedback can reap great benefits if done with intention.…”
Section: -Listening and Empathy Come Firstmentioning
confidence: 88%
See 1 more Smart Citation
“…Methodological approaches can range from our simple Q&A format to the World Health Organization's highly sophisticated machine learning-driven social listening of large social media platforms. 5 Our methods provide proof-of-concept that even simple efforts to elicit community feedback can reap great benefits if done with intention.…”
Section: -Listening and Empathy Come Firstmentioning
confidence: 88%
“…Cultivating a two-way dialogue, termed “social listening” in infodemiology research, 5 is also considered a best practice in the broader health communication and promotion literatures, 6,7 and is already familiar to and embodied by health promotion professionals. Methodological approaches can range from our simple Q&A format to the World Health Organization’s highly sophisticated machine learning-driven social listening of large social media platforms.…”
Section: Let’s Learnmentioning
confidence: 99%
“…The research gaps that were identified have also guided the WHO in the review of the COVID-19 research blueprint [ 42 ] and in the development of partnerships that foster filling of research gaps and for translation of evidence into use by health authorities and other partners [ 28 , 43 ]. The WHO has also applied evidence and infoveillance methods to inform its own work and contribute to the development of metrics for health authorities [ 18 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their battle against misinformation, health organizations should change the pejorative framing of the term "infodemic" into something more neutral so as not to generate resistance or a boomerang effect among certain groups. For example, the WHO can use its AI-powered tool 86 based in its social listening approach 87 to ask subgroups in each country to suggest other names for the information and can consult with those who are hesitant or skeptical regarding how to reframe the information.…”
Section: The Battle Against Misinformation Challenge: Erroneous or False Information Can Trigger Skepticism And Resistancementioning
confidence: 99%
“…128 The public sphere would function better as a system in times of crisis if the WHO were to interact with various groups in the public on an ongoing basis, like in the WHO recent social listening approach. 86,87 The culture of inclusion should be established not only during crises, but as a systemic continuum for digital crowdsourcing risk communication management.…”
Section: Recommendation: Use Crowdsourcing To Solve Complex Global Health Problemsmentioning
confidence: 99%